The Readiness of Minang Weaving Towards Halal Fashion Adoption: A Clustering Analysis of Toe Framework - Ratni Prima Lita; Nilda Tri Putri; Meuthia Meuthia; Devi Yulia Rahmi (Journal of Applied Engineering and Technological Science (JAETS), 2023)
This research focuses on clustering the readiness of halal practice implementation in Minang weaving businesses, then based on the clusters that are very ready, it is then carried out the identification of the determinant factors of the readiness to implement the Halal Assurance System in Minang weaving businesses. Sampling was conducted using the non-probability sampling technique through purposive sampling from 103MSMEs of weaving in West Sumatra. The results of this research through K-means cluster analysis show that the grouping of Technology, Organization, Environment (TOE ) halal adoption in weaving MSMEs consists of 6 readiness groups, namely termination (15 MSMEs), maintenance (43 MSMEs), action (23 MSMEs), preparation (13 MSMEs), contemplation ( 2 MSMEs), pre-contemplation (7 MSMEs) spread across five cities/regencies in West Sumatra (Sawahlunto City and 50 Cities Regency which consists of 34 MSMEs respectively, 30 MSMEs from Tanah Datar Regency, 3 MSMEs from Sijunjung Regency, and 2 MSMEs from Payakumbuh City). Of the three determinants of TOE adoption tested, MSMEs' perceptions of technology readiness through the dimensions of compatibility and perceived benefits are higher than organizational and environmental factors. This research has theoretical and practical implications through exploration of the TOE model so that the results of this study can become a further research agenda in encouraging halal certification through developing a halal adoption strategy based on HAS 23000 in weaving MSMEs in West Sumatra.